Towards a longitudinal outlook on industry transition management - Kwok L. Shum; Fumio Kodama; Tomoatsu Shibata (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Innovation has been and continues to be an important theme in management literature, and almost any improvement upon the status quo could be regarded as some sort of innovation. Such an improvement could be made in terms of an increase of efficiency for an existing process or the creation of something new, such as a new process, product, position (perception), or even a paradigm (mental model) (Tidd, Bessant et al., 2005). Not all innovations are therefore the same. Some are more disruptive, while others are incremental, reinforcing the existing order of things. This paper discusses the evolution of innovation as a management concept in the context of a physical product or technology and studies innovation from a longitudinal perspective, i.e., from a single physical product to a product family to smart services associated with the physical products and to the fourth industrial revolution (Industry 4.0) in which physical products are now part of an extensive industrial network, namely the internet of things. How does the theme of innovation (management) change and evolve during this industry transition? More importantly, what are the managerial implications for innovating in the era of Industry 4.0?
Keywords: 650; product-centric innovation; product platform; service innovations; smart services; digital platform; industry 4.0